Human-specific duplicate CHRFAM7A gene is associated with more severe osteoarthritis and amplifies pain behaviours. Issue 5 (10th January 2023) - Courties, Alice; Olmer, Merissa; Myers, Kevin; Ordoukhanian, Phillip; Head, Steven R; Natarajan, Padmaja; Berenbaum, Francis; Sellam, Jérémie; Lotz, Martin K
Abstract : Objectives: CHRFAM7A is a uniquely human fusion gene that functions as a dominant negative regulator of alpha 7 acetylcholine nicotinic receptor (α7nAChR) in vitro. This study determined the impact of CHRFAM7A on α7nAChR agonist responses, osteoarthritis (OA) severity and pain behaviours and investigated mechanisms. Methods: Transgenic CHRFAM7A (TgCHRFAM7A) mice were used to determine the impact of CHRFAM7A on knee OA histology, pain severity in OA and other pain models, response to nAchR agonist and IL-1β. Mouse and human cells were used for mechanistic studies. Results: Transgenic (Tg) TgCHRFAM7A mice developed more severe structural damage and increased mechanical allodynia than wild type (WT) mice in the destabilisation of medial meniscus model of OA. This was associated with a decreased suppression of inflammation by α7nAchR agonist. TgCHRFAM7A mice displayed a higher basal sensitivity to pain stimuli and increased pain behaviour in the monoiodoacetate and formalin models. Dorsal root ganglia of TgCHRFAM7A mice showed increased macrophage infiltration and expression of the chemokine fractalkine and also had a compromised antinociceptive response to the α7nAchR agonist nicotine. Both native CHRNA7 and CHRFAM7A subunits were expressed in human joint tissues and the CHRFAM7A/CHRNA7 ratio was increased in OA cartilage. Human chondrocytes with two copies of CHRFAM7A had reduced anti-inflammatory responses to nicotine. Conclusion: CHRFAM7A is an aggravating factor for OA-associated inflammation and tissue damage and a novel genetic risk factor and therapeutic target for pain.